A Titrimetric Estimation of Ammonium Thiocyanate, Thiourea, N-Phenylthiourea,N, N´ -Diphenylthiourea and Thiosemicarbzide with Ammonium Hexanitratocerate(IV) in Perchloric Acid Medium - Madhava Rao, B.; Kulkarni, M.J. (Asian Journal of Chemistry, 2010)
By applying suitable conditions viz., slightly elevated temperatures (45º to 55ºC) for different intervals of time in 1.0M perchloric acid medium, the indirect titrimetric estimations of ammonium thiocyanate, thiourea, N-phenylthiourea, N,N´-diphenylthiourea and thiosemicarbazide with cerium(IV) as an oxidant can be achieved. These estimations are fundamentally based on the established stoichiometries of the oxidation reactions of the aforementioned organic substrates. The technique adopted in all the cases is the addition of a known excess of cerium(IV) to a requisite volume of an aqueous solution of the organic substrate and back-titration of the unreacted cerium(IV) with iron(II) solution to a potentiometric end-point or by employing a suitable redox indicator e.g., ferroin.